An alternative approach to explaining unemployment: evidence from a three country study - Αλεξίου, Κωνσταντίνος (SPOUDAI Journal of Economics and Business, 2000)
Creating sustained economic growth and tackling unemployment remain centre-stage in economic policy debate across the globe and look set to remain there for the foreseeable future. As a result, much academic debate has been developed regarding this macroeconomic problem, as well as policy measures to confront it. This study aims at gaining an insight into the relationship between capital stock and employment as one of the main factors that exacerbates the existing problem. An econometric analysis will provide us with some interesting results, concerning the behaviour of the two economic variables in question, over a period of time. More specifically, our econometric part will be concentrating on the analysis of the data of three European countries the UK, Germany, and France. JEL Classification: B22, E12